Definition and recommendations for advance care planning: an international consensus supported by the European Association for Palliative Care. Issue 9 (September 2017) - Rietjens, Judith A C; Sudore, Rebecca L; Connolly, Michael; van Delden, Johannes J; Drickamer, Margaret A; Droger, Mirjam; van der Heide, Agnes; Heyland, Daren K; Houttekier, Dirk; Janssen, Daisy J A; Orsi, Luciano; Payne, Sheila; et al.
Summary: Advance care planning (ACP) is increasingly implemented in oncology and beyond, but a definition of ACP and recommendations concerning its use are lacking. We used a formal Delphi consensus process to help develop a definition of ACP and provide recommendations for its application. Of the 109 experts (82 from Europe, 16 from North America, and 11 from Australia) who rated the ACP definitions and its 41 recommendations, agreement for each definition or recommendation was between 68–100%. ACP was defined as the ability to enable individuals to define goals and preferences for future medical treatment and care, to discuss these goals and preferences with family and health-care providers, and to record and review these preferences if appropriate. Recommendations included the adaptation of ACP based on the readiness of the individual; targeting ACP content as the individual's health condition worsens; and, using trained non-physician facilitators to support the ACP process. We present a list of outcome measures to enable the pooling and comparison of results of ACP studies. We believe that our recommendations can provide guidance for clinical practice, ACP policy, and research.